Insecticide Resistance in Agricultural Pests: Mechanisms, Case Studies, and Future Directions - Khudhair, Ihsan; Abbood, Naseer Malaky; El-Amier, Yasser Ahmed Mahmoud (University of Thi-Qar Journal of Science, 2025)
Pesticide resistance is an escalating global challenge that threatens agricultural productivity, food security, and the sustainability of pest control methods. Over 600 insect species have developed resistance, compromising the effectiveness of chemical controls and exacerbating pest outbreaks. Species such as Helicoverpa armigera and Bemisia tabaci serve as prominent examples of pests displaying this growing resistance problem. This study aims to explore the underlying mechanisms of pesticide resistance in key agricultural pests, identify the major contributing factors, assess the effectiveness of current management strategies, and examine potential future tools and technologies for combating resistance. The study integrates data from global case studies, specifically focusing on Helicoverpa armigera in India and Bemisia tabaci in China. It also synthesizes information on various resistance mechanisms, including metabolic, target-site, penetration, and behavioral processes. Several resistance management strategies, such as pesticide rotation, integrated pest management (IPM), and refuge policies, are evaluated for their effectiveness. Metabolic and target-site resistance mechanisms are particularly prevalent in resistant insect populations. Contributing factors include overuse of single pesticide classes, sub-lethal dosages, inadequate treatment regimens, and monoculture farming. IPM and pesticide rotation employing different modes of action are among the most effective current strategies. Emerging technologies RNA interference (RNAi) and CRISPR gene editing , offer promising new approaches. Addressing pesticide resistance requires a comprehensive, multi-faceted strategy that incorporates genetic tools, real-time monitoring, biopesticide development, and stronger regulatory frameworks. International cooperation, farmer education, and scientifically informed policies will be critical to future success.